1985
DOI: 10.1152/ajpendo.1985.249.2.e219
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal-stimulated and stress-induced ACTH release in rats is mediated by ventral noradrenergic bundle

Abstract: Female rats were bilaterally injected with 3 micrograms of 6-hydroxydopamine (6-OHDA) dissolved in 0.2 microliter saline, via a glass micropipet stereotaxically implanted into the ventral noradrenergic-ascending bundle (VNAB). This bundle conveys most of the catecholaminergic innervation to the paraventricular nuclei and originates from the locus coeruleus and from two medullary groups of neurons (A1 and A2). Two weeks after injection, and 1 wk after the subsequent implantation of an arterial cannula, serial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 35 publications
8
73
0
Order By: Relevance
“…These observations suggest that the IIH-induced CRF and AVP release into HPB is mediated through extrahypothalamic pathways. We and others have shown recently that central catecholamines, originating from the brainstem nuclei, have a stimulatory effect on hypothalamic CRF secretion in the rat (27,28). Interestingly, hypothalamic norepinephrine activity is increased during IIH in rats, and this increase parallels the variation in plasma corticosterone (29).…”
Section: Ram N 566mentioning
confidence: 71%
“…These observations suggest that the IIH-induced CRF and AVP release into HPB is mediated through extrahypothalamic pathways. We and others have shown recently that central catecholamines, originating from the brainstem nuclei, have a stimulatory effect on hypothalamic CRF secretion in the rat (27,28). Interestingly, hypothalamic norepinephrine activity is increased during IIH in rats, and this increase parallels the variation in plasma corticosterone (29).…”
Section: Ram N 566mentioning
confidence: 71%
“…Mechanisms through which the HPA system may be restrained during sleep include activation of the mineralocorticoid-receptor [6]and reduced electrical activity of noradrenergic brainstem nuclei [3]. The latter could, by removing noradrenaline-mediated facilitation of ACTH release [35], contribute to the blunted response to intravenous CRH and at the same time favor α 2 -receptor-mediated GHRH release [1]. In contrast, intravenous administration of GHRH will act primarily at the pituitary level, leaving afferent pathways unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Morgan and Curran,199 l), in brain regions known to influence basal and stress-induced activity of this axis including the cortex, hippocampus, hypothalamus, septum, amygdala, and brainstem. Lesion and electrical stimulation studies have indicated that certain brainstem (Szafarczyk et al, 1985;Sawchenko, 199 1) and hypothalamic (Dohanics et al, 1986;Richardson-Morton et al, 1989) nuclei positively influence basal and stress-induced activity of the PA-axis. In contrast, specific cortical regions, hippocampus, and the lateral septal area are involved in inhibitory regulation of this axis (Seggie et al, 1973;Sapolsky et al, 1984;Saphier and Feldman, 1987;Herman et al, 1990).…”
Section: Discussionmentioning
confidence: 99%